Emancipation of slaves in Saudi Arabia - Alzahrani, Hissah Jamaan (Journal of Humanities & Social Sciences, 2021)
Each era has its values, concepts, circumstances, and beliefs, which it is instinctive of, and it also has the logic of change and transformation dependent on the strengths and weaknesses. And all the events mentioned in the research can only be read in the context of their movement and historical roles subject to the concepts and values of their time and place. There are groups that were often absent from the history record, and they were wrongly judged in their absence as if they were outside history, the reason for this is that their historical experience and their stories were closer to being blocked. Many references were written in the history of the Hijaz, Najd and the Gulf, and their political, economic and social lives were recorded, and they were well documented without being accompanied by sufficient documentation of the history of the silent and its marginalized groups (slaves). This study talks about the development of the stages of the emancipation of slaves in the Kingdom of Saudi Arabia, and what was this trade in general? How did you become in the Saudi era? The study will talk about the importance of slavery and the economic cycle, in addition to their social role. It is not our intention to uncover the depths except that- with the courage of the researcher and the integrity of science- we rearrange the memory of our nation around this category from its entry into the land of the island until its liberation.